2008
DOI: 10.1007/s00204-008-0298-6
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of oxime 3-(phenylhydrazono) butan-2-one

Abstract: Oximes are a class of compounds normally used to reverse the acetylcholinesterase (AChE) inhibition caused by organophosphates (OPs). Conversely, researches focusing on the possible antioxidant properties of these compounds are lacking in the literature. The aim of this study was to investigate the potential antioxidant and toxic properties of 3-(phenylhydrazono) butan-2-one oxime in mice. In vitro, hydrogen peroxide-induced lipid peroxidation was decreased by low concentrations of the oxime (0.1-1.0 microM); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
0
14
2
Order By: Relevance
“…Additionally, Puntel et al . showed that 3‐(phenylhydrazono)‐butan‐2‐one oxime was able to decrease TBARS production in brain homogenates induced by malonate and iron. After these considerations, novel insight into the principles of oxime bioactivity can be given.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Puntel et al . showed that 3‐(phenylhydrazono)‐butan‐2‐one oxime was able to decrease TBARS production in brain homogenates induced by malonate and iron. After these considerations, novel insight into the principles of oxime bioactivity can be given.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, an oxime (3‐(phenylhydrazono) butan‐2‐one oxime) was found to act as a potential antioxidant in vitro and in mice (Puntel et al ., 2008). In vitro, hydrogen peroxide‐induced and malonate‐iron mixture‐induced lipid peroxidations were decreased by low concentrations of this oxime (0.1–1.0 μ m ).…”
Section: Discussionmentioning
confidence: 99%
“…On heating, a dark orange product was formed, which was collected by filtration, washed with water and dried in a vacuum (FP 160-163°C). 28 (3Z)-5-Chloro-3-(hydroxyimino)indolin-2-one oxime (Cℓ-HIN) ( Figure 1B) was synthesized as described by Martins and collaborators, with an equimolar mixture of 5-chloroisatin and hydroxylamine chlorhydrate in ethanol. 29 The reaction medium was acidified with acetic acid and placed under reflux (135°C) for 5 h. After that, the reaction was vacuum-filtered and the compound was isolated as a golden yellow precipitate which, in sequence, was washed with cold distilled water (FP 252-274°C).…”
Section: Synthesis Of Oxime and Isatin Derivativesmentioning
confidence: 99%